2020
DOI: 10.1080/15384101.2020.1792127
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA LINC00467 inhibits glioma cell progression via modulation of E2F3 targeted by miR-200a

Abstract: Studies have found that LINC00467 is an important regulator of cancer. However, the function of LINC00467 in glioma cell is unclear. Therefore, this experimental design based on LINC00467 to explore its mechanism of action in glioma cell. RT-qPCR was used to detect the expression of LINC0046 and miR-200a in glioma cell lines. MTT assay, Edru assay and Transwell assay and flow cytometry were used to detect the effects of LINC0046 and miR-200a on PC cell proliferation, migration and apoptosis. Target gene predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…LINC00467 expression is aberrantly upregulated in multiple tumor tissues and can enhance cell proliferation in neuroblastoma ( 15 ), lung cancer ( 16 ), and glioma cells ( 17 ). LINC00467 expression is closely associated with worse prognosis of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00467 expression is aberrantly upregulated in multiple tumor tissues and can enhance cell proliferation in neuroblastoma ( 15 ), lung cancer ( 16 ), and glioma cells ( 17 ). LINC00467 expression is closely associated with worse prognosis of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several initiated signaling pathways, including linc00467/miR-20b-5p/cyclin D1 pathway [ 20 ] and STAT1-induced upregulation of linc00467 promoted lung adenocarcinoma progression through epigenetically suppressing dickkopf WNT signaling pathway inhibitor 1 to activate Wnt/β-catenin signaling [ 16 ]. Regarding glioma, studies have demonstrated that linc00467/DNA methyltransferase 1/p53 pathway, and linc00467/miR-200a/E2F transcription factor 3 pathway might be involved in the occurrence of glioma [ 21 , 30 ]. In this study, we have further discovered that linc00467 was significantly upregulated in GC cell lines compared with control GES-1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, concordant with our results, silence of LINC00467 has been demonstrated to curb malignant properties of GC cells by targeting microRNA-7-5p [ 9 ]. Of note, LINC00467 knockdown diminished glioma U87 and U251 cell malignant properties [ 35 , 36 ]. In addition, ectopically expressed LINC00467 contributed to elevation of cell malignant properties in osteosarcoma [ 37 ].…”
Section: Discussionmentioning
confidence: 99%